2019
DOI: 10.1108/vjikms-11-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corporate social responsibility on organizational performance

Abstract: Purpose -This paper aims to examine the potential moderating effect of knowledge management on the influence of corporate social responsibility (CSR) on organizational performance.Design/methodology/approach -Questionnaire data were collected from 170 distinct companies in Taiwan.Findings -The results confirm the positive influence of CSR on organizational performance. There are also some interesting moderating effects of knowledge management in the CSR-performance relationship.Originality/value -A major contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 83 publications
0
13
1
Order By: Relevance
“…The traditional CSR approach refers to the social and green dimensions, guiding the enterprises to achieve their long-term GP [62]. Several studies support a predominant approach to CSR on GP [31,[68][69][70][71] by proving the positive influence of CSR on organizational performance [72]. This underlying relationship revealed that socially responsible firms provide economic benefits to organizations, thereby reinforcing the relationship between CSR and GP [73].…”
Section: Corporate Social Responsibility and Green Performancementioning
confidence: 99%
“…The traditional CSR approach refers to the social and green dimensions, guiding the enterprises to achieve their long-term GP [62]. Several studies support a predominant approach to CSR on GP [31,[68][69][70][71] by proving the positive influence of CSR on organizational performance [72]. This underlying relationship revealed that socially responsible firms provide economic benefits to organizations, thereby reinforcing the relationship between CSR and GP [73].…”
Section: Corporate Social Responsibility and Green Performancementioning
confidence: 99%
“…Although firms are increasingly embracing CSR policies and practices (Hou, ; Tang & Gekara, ) to build social legitimacy and foster stakeholder relationships, the empirical research revealed inconclusive findings regarding the impact of CSR practices on organizational performance (OP). For instance, the relationship between CSR and OP has been found positive in some studies (Ling, ; Naseem, Shahzad, Asim, Rehman, & Nawaz, ; Reverte, Gómez‐Melero, & Cegarra‐Navarro, ), others suggested rejection or disassociation (Crisóstomo, de Souza Freire, & Cortes de Vasconcellos, ; Malcolm, Khadijah, & Amiruddin, ). With regard to the inconclusive findings, some scholars have questioned the approach used by mainstream research (Khan, Ali, Olya, Zulqarnain, & Khan, ; Mehralian, Nazari, Zarei, & Rasekh, ; Saeidi, Sofian, Saeidi, Saeidi, & Saaeidi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the academic literature, CSR and KM are considered to be closely linked (Ling, 2019). Thus, when companies invest in CSR policies, the application of KM can also enable them to reduce resource waste, improve resource utilization and improve operational processes (Xu et al, 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%